Classroom-Based Assessment in EFL Writing Classes - Yamon Sudamara (Universitas Tadulako, 2021)
A Classroom Action Research at the 9th-Year Students of SMP Negeri Model Terpadu Madani Palu, 2019/2020 academic year aimed at finding out the students’ real portrait English writing performave. The truism showed that the teachers of English had not found effective assessment strategy to elicit accurate assessment results about their students’ actual performance. Therefore, it is necessary to develop and find a new assessment strategy to solve this problem. It is found that the efective assessment strategy is classroom-based assessment with the following procedures. First, preparation or introductory step that include three activities: (1) introducing the idea of classroom-based assessment and procedure of its implementation to students, (2) specifying/ informing teaching and assessment objectives and selecting writing tasks, and (3) specifying aspects to be assessed and criteria of assessment. Second, assessment activities include four activities: (1) observing students’ performances in writing process, (2) assessing students’ knowledge on basic skills for paragraph writing, (3) getting students’ responses and feelings toward the learning activities, and (4) assessing/evaluating students’ writing product as product assessment. For Junior High students, holistic assessment is recommended